Simple ultrasonic construction of AgBr/Ag3PO4 hybrid quasi‐microcube with improved visible‐driven photocatalytic property. (1st July 2013) - Xie, Jinsong; Zhao, Difang; Tian, Changan; Han, Chengliang; Zhang, Hui
Abstract : AgBr/Ag3 PO4 composite quasi‐microcubes were fabricated by a simple ultrasonic synthesis method, in which hexadecyltrimethylammonium bromide was used as Br resource and surfactant. The structures and morphologies of the as‐obtained product were initially characterised by X‐ray diffraction, field emission scanning electron microscopy and energy dispersive X‐ray analysis spectroscopy. The ultraviolet–visible diffuse reflectance spectrum of the as‐obtained products demonstrated that this hybrid structure exhibits an enhanced absorption ability in the visible region. Furthermore, the composite products exhibit much higher photocatalytic performance and stability on degradation of rhodamine B dye under the stimulated sunlight irradiation compared with pure AgBr and Ag3 PO4 .